폐쇄성 폐질환과 동반된 폐쇄수면무호흡증의 치료 - 김성수; 박순민 (Sumyŏn--chŏngsin saengni, 2023)
OSA환자들은 COPD, 천식 등을 함 께 가지고 있는 경우가 많이 있고, 이러한 경우 어느 한 질 환의 진단 및 치료 대하여 간과하게 되면, 전반적인 증상 조절 및 예후에 영향을 미치게 된다. OSA 환자들의 증상은 다 양하며, 때로는 천식, COPD 등의 증상과 구분이 어려울 수 있다. 따라서, OSA 의심 환자를 진료할 때에는 기침, 가래, 숨찬 증상 등의 호흡기 증상 및 흡연력, 알레르기 질환의 병력 등에 대한 확인을 하며, 가슴 X-ray를 확인하고, 만성 폐질환 동반 가능성이 의심된다면 폐기능검사(pulmonary function test) 등을 통하여 적극적으로 감별하는 것이 중요하겠다. 마찬가지로, COPD가 의심되어 내원한 환자들도 주간졸림, 코골이, 수면 중 무호흡, 수면 중 각성여부와 저항성 고혈압, 당뇨병, 심혈관계질환, 뇌혈관계질환 등의 동반 질환 등을 평가 하여 OSA를 의심하고 진단하는 것이 환자의 예후에 도움이 되겠다. Obstructive lung diseases encompass a group of chronic respiratory conditions characterized by airflow limitation. This category includes chronic obstructive pulmonary disease (COPD), asthma, and several other diseases. It is known that the likelihood of sleep-disordered breathing increases in patients with obstructive lung diseases, and vice versa. Obstructive sleep apnea, the most common sleep-disordered breathing, and COPD mutually influence each other concerning disease occurrence, symp¬toms, severity, and prognosis. Moreover, the coexistence of both in Overlap syndrome (OS) demonstrates a worse prognosis compared to each condition separately. Asthma also shares common risk factors with OSA, and each condition affects the se¬verity and treatment management of the other. When treating patients with both chronic respiratory diseases and sleep-related breathing disorders, it is crucial not to focus solely on one group of conditions. Sensitively diagnosing both conditions and im¬plementing appropriate treatments at the right time is important. KCI Citation Count: 0